The Effect of Digitalization on Economic Development in Bengkalis Regency - Siti Saidah; Shofiyan Hidayat; Nur Jihan Farisha; M Abdul Gapur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Digitalization in the economic sector certainly cannot be separated from the term digital entrepreneurship, which is often associated with